Evaluating Cloud Properties at Scott Base: Comparing Ceilometer Observations With ERA5, JRA55, and MERRA2 Reanalyses Using an Instrument Simulator - McDonald, Adrian J.; Kuma, Peter; Panell, M.; Petterson, Orlon K. L.; Plank, Graeme E.; Rozliaiani, M. A. H.; Whitehead, Luke E. (Journal of Geophysical Research: Atmospheres, 2025)
This study compares CL51 ceilometer observations made at Scott Base, Antarctica, with statistics from the ERA5, JRA55, and MERRA2 reanalyses. To enhance the comparison we use a lidar instrument simulator to derive cloud statistics from the reanalyses which account for instrumental factors. The cloud occurrence in the three reanalyses is slightly overestimated above 3 km, but displays a larger underestimation below 3 km relative to observations. Unlike previous studies, we see no relationship between relative humidity and cloud occurrence biases, suggesting that the cloud biases do not result from the representation of moisture. We also show that the seasonal variation of cloud occurrence and cloud fraction, defined as the vertically integrated cloud occurrence, are small in both the observations and the reanalyses. We also examine the quality of the cloud representation for a set of weather states derived from ERA5 surface winds. The variability associated with grouping cloud occurrence based on weather state is much larger than the seasonal variation, highlighting weather state is a strong control of cloud occurrence. All the reanalyses continue to display underestimates below 3 km and overestimates above 3 km for each weather state. But the variability in ERA5 statistics matches the changes in the observations better than the other reanalyses. We also use a machine learning scheme to estimate the quantity of supercooled liquid water cloud from the ceilometer observations. Ceilometer low-level supercooled liquid water cloud occurrences are considerably larger than values derived from the reanalyses, further highlighting the poor representation of low-level clouds in the reanalyses.
Keywords: Antarktis; dataanalyse; forskningsstasjoner; meteorologi

Field comparison of Antarctic krill (Euphausia superba) backscatter and aggregation types using NORTEK and SIMRAD echosounders - Annasawmy, Pavanee; Horne, John K.; Reiss, Christian S.; Cutter, George R.; Macaulay, Gavin J. (ICES Journal of Marine Science, 2024)
Temporal distributions of Antarctic krill (Euphausia superba) density and aggregation types were characterized and compared using Nortek Signature100 and SIMRAD Wideband Autonomous Transceiver (WBAT) upward-looking echosounders. Noise varied between the two echosounders. With the Signature100, it was necessary to correct data for background, transient, and impulse noises, while the WBAT data needed to be corrected for background noise only. For selected regions with no visible backscatter, the signal-to-noise ratio of Sv values (i.e. the ratio between the signal and the background noise level) did not vary between the two echosounders. Surface echo backscatter was similar during similar time periods. Descriptive metrics were used to quantify spatial and temporal krill vertical distributions: volume backscatter, mean depth, center of mass, inertia, equivalent area, aggregation index, and proportion occupied. Krill backscatter density differed between the two instruments but was detected at similar mean depths. Krill aggregations were identified at each mooring location and classified in three types based on morphological characteristics. Each type of aggregation shape differed at the two spatially separated moorings, while the acoustic density of each aggregation type was similar. The Signature100 detected a lower number of krill aggregations (n = 133) compared to the WBAT (n = 707). Although both instruments can be used for autonomous deployment and sampling of krill over extended periods, there is a strong caveat for the use of the Signature100 due to significant differences in noise characteristics and krill detection.
Keywords: Sørishavet; dataanalyse; ekkolodd; fiskerier; krill; marin biologi; plankton

KRILLSCAN: An automated open-source software for processing and analysis of echosounder data from the Antarctic krill fishery - Menze, Sebastian; Macaulay, Gavin J.; Zhang, Guosong; Lowther, Andrew D.; Krafft, Bjørn A. (Fisheries Management and Ecology, 2024)
Krillscan software was developed to automatically process echosounder data and achieve an accelerated and transparent analysis of backscatter data that allows calculation of target biomass. Herein, the fishery for Antarctic krill (Euphausia superba, Henceforth Krill) was used as a case study to develop the approach. Implementation of a sustainable management strategy for the krill fishery is complicated by a lack of regularly updated krill abundance data on spatiotemporal scales of the fishery. To increase krill biomass data availability, automatic echosounder data processing and swarm detection software was tested against traditional manual scrutinization with LSSS software and agreed with only minor offsets in estimated nautical area scattering coefficients. In addition to automatic processing and data transfer, Krillscan also has a graphical user interface to supervise automatic krill swarm detection. Echogram size can be compressed up to 100 times and raw data are processed faster than generated, thereby enabling near-real time analysis and data transfer. Compressed data can be transmitted online to allow fishing vessels to conduct surveys without having scientific personnel with special expertise on board.
Keywords: Sørishavet; dataanalyse; ekkolodd; fiskerier; krill; plankton

National and institutional productivity and collaboration in Antarctic science: an analysis of 25 years of journal publications (1980–2004) - Dastidar, Prabir G. (Polar Research, 2007)
Journal publications on Antarctic science were analysed for a period of 25 years (1980–2004) through a set of scientometrics and network analysis techniques. The study is based on 10 942 records (research articles, review articles, letters, etc.) with the word fragment “antarc*” in the title published in 961 international, peer-reviewed journals and retrieved from Thomson Scientific’s Science Citation Index database. During the period under investigation, productivity increased threefold and there was a 13-fold increase in journal publications co-written by authors from different countries. The five nations with the highest output were the USA (with 26.7% of the total output), the UK (13.8%), Australia (9.7%), Germany (8.8%) and Italy (6.0%). The top five institutions in terms of journal publications were the British Antarctic Survey (972 publications), the Alfred Wegener Institute of Polar and Marine Research, Germany (475), the Australian Antarctic Division (312), the University of Tasmania, Australia (305), and the National Aeronautics and Space Administration, USA (293).
Keywords: Antarktis; dataanalyse; forskning; scientometri; tidsskriftspublikasjoner